PERBEDAAN TUMBUHAN PERKEMBANGBIAKAN VEGETATIF ALAMI DAN BUATAN: STUDI EKSPERIMEN SEDERHANA - Salsa Septiani; Pira Astuti; Nurul Hasanah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to identify the differences between natural and artificial vegetative propagation in plants through simple experiments conducted in elementary schools. The research employed a qualitative approach with a descriptive design. Data collection techniques included observation and documentation of students' practical activities. The results revealed fundamental differences between natural and artificial vegetative propagation. Natural vegetative propagation occurs without human intervention, as seen in bulbs, shoots, and rhizomes, while artificial vegetative propagation involves human intervention, such as grafting, cutting, and budding. The experimental activities demonstrated that hands-on learning enhances students' understanding of science concepts in a more contextual and meaningful manner. This study also contributes to the application of differentiated instruction and scientific approaches in primary education.